Current Issues and Prospects of Modern Higher Legal Education in Conditions of the Fight against COVID-19 - Myronets, Oksana M.; Danyliuk, Ivan V.; Dembytska, Nataliia M.; Frantsuz-Yakovets, Tetiana A.; Dei, Maryna O. (Cuestiones Políticas, 2020)
The purpose of the document is to determine the current problems and the possible directions for the development and improvement of higher legal education in the modern challenges and conditions of the pandemic and post-pandemic of COVID-2019, under the hypothesis that the upcoming emergency is affirmed again. world order. General-scientific and special-legal methods of cognition have been used. Through the use of the dialectical method, the current problems of modern legal education have also been identified, their foundations have been investigated and instructions have been sought to improve legal education and the quality of young lawyers in the educational environment of the pandemic. In conclusion, it is highlighted that the findings found in the research can be useful for higher education teachers who are constantly adapting to the new conditions of professional activity in the field of legal education, in the scene of pandemic and the ordering after the pandemic, with particular emphasis on specialists focused on developing suggestions and improving the quality of legal education in the context of the global challenges imposed by COVID-2019.